STUDI ANALISIS SETTING FILTER AKTIF TERHADAP PENINGKATAN KUALITAS DAYA LISTRIK DI GEDUNG PERKULIAHAN FAKULTAS TEKNIK UNIVERSITAS UDAYANA JALAN PB SUDIRMAN - I Gede Dyotha Yogadipha Bagas; I Wayan Rinas; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2020)
Harmonics are disturbances in the electric power system in the form of distortions incurrent and voltage waves caused by the formation of waves with a interger multipliedfrequency of the fundamental frequency. Total Harmonic Distortion (THD) is the amount of theeffective value of waves affected by harmonics that affect the occurrence of electrical powerlosses. This study discusses the analysis of current THD in the lecture building at the Faculty ofEngineering, Udayana University, Jalan PB Sudirman. The simulation is carried out underexisting conditions and when operating an active filter will show the results of the THD currentthen adjusted to the IEEE 519-2014 standard. Then an analysis of power losses due toharmonics is performed. THDi in the existing conditions for phase R = 15.44%, S = 15.6%, andT = 11.42% while the active filter operation is at phase R = 2.41%, S = 2.69%, and T = 2.99%.Power losses due to haronisa interference under existing conditions were 12,6 % and on theactive filter operating conditions were 0,037 %.